The Challenges of the Sharia Economy and Businesses In Facing the Coronavirus Endemic and Circular Economy In Indonesia - Jam'an; Asdar; Nur Sandi Marsuni (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
The outbreak of the coronavirus pandemic has had significant negative effects on various sectors, including the economy in Indonesia. These adverse impacts have also extended to the Sharia-based financial and business sectors. This study aims to identify and explore the challenges faced by the Islamic economy and industry in the aftermath of the coronavirus pandemic and its on going endemic nature. A qualitative research approach was used, drawing from various studies and prior research findings. The study reveals a decline in several Sharia products and challenges in Sharia production, largely due to a heavy dependence on imported raw materials. This issue continues to affect businesses within the Sharia-based economic and financial sector, ultimately limiting investment opportunities. Consequently, with government support, actors in the Sharia economy and business sector need to reassess growth targets and leverage digital technology to recover from the economic disruptions caused by the coronavirus endemic. Research Implications Sharia-based businesses should diversify supply chains to reduce dependence on imports and adopt digital technology to boost resilience and competitiveness. The government can support recovery by providing incentives and fostering innovation in Sharia-compliant products to ensure sustainable growth.